1998
DOI: 10.1017/s095026889800154x
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological evaluation of 1989–91 mass vaccination campaigns against measles, in Italy

Abstract: In 1989-91 anti-measles vaccination campaigns were conducted in several Italian regions to vaccinate all children aged between 13 months and 10-12 years without a history of measles or measles vaccination. This study was conducted to evaluate serological status after the mass vaccination campaigns. In 1994, capillary blood samples were collected from randomly selected children, aged 2-14 years, living in 13 local health units. Antibody titres were determined by ELISA. Blood spot samples were analysed for 4114 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The high measles seroprevalence in these mostly unvaccinated students is hardly a surprise. Our results are supported by a study conducted on pupils born in the late 1980s in which 50% of children from 36 months in Southern Italy to 5-6 years in Northern Italy (Grandolfo et al 1998) achieved natural infection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The high measles seroprevalence in these mostly unvaccinated students is hardly a surprise. Our results are supported by a study conducted on pupils born in the late 1980s in which 50% of children from 36 months in Southern Italy to 5-6 years in Northern Italy (Grandolfo et al 1998) achieved natural infection.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, rubella seropositivity was always lower compared to the other European studies (WHO 2005a, b;Dominguez et al 2006). The percentage of those reporting to have had measles and who were immune is very similar to the percentage reported in a study carried out in Italian children born before 1990 (Grandolfo et al 1998), but, as multivariate logistic regression suggests and other surveys confirm (Baer et al 2005;Murray and Linch 1988), historical information on measles, mumps and rubella infection cannot be a reliable predictor. The high measles seroprevalence in these mostly unvaccinated students is hardly a surprise.…”
Section: Discussionmentioning
confidence: 52%
“…The results indicate that although measles is mainly a disease of childhood, there were some individuals who suffered from measles beyond 15 years of age and others up to the age of 59 years which was consistent with findings reported from elsewhere (4)(5)(6). This observation suggests changing pattern in the epidemiology of measles in Tanzania.…”
Section: Discussionsupporting
confidence: 90%
“…It has previously been demonstrated that dried blood spots are a feasible alternative to venous blood as a specimen for use in investigations for measles virus antibodies (2,3,5,10). The present study demonstrates for the first time the feasibility of laboratory diagnosis of measles by use of dried blood specimens with a commercial assay.…”
Section: Discussionmentioning
confidence: 55%